2012
DOI: 10.1007/s00011-012-0510-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Th17 cell frequency concomitant with decreased Foxp3+ Treg cell frequency in the peripheral circulation of patients with carotid artery plaques

Abstract: Our investigation demonstrated that there is a Th17/Treg functional imbalance in patients with unstable carotid atherosclerotic plaques. Th17 cells may promote atherogenesis, while Treg cells may have a protective role against atherosclerosis plaques. An imbalance of Th17/Treg cells may offer a new direction for the treatment of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…However, the number and function of these cells decreases both in plaques and in circulation as disease progresses, consistent with a breakdown in tolerance and the appearance of proinflammatory T cells (9)(10)(11)(12). The Li study confirmed this decline in circulating Treg numbers alongside the expression levels of TGF-β and FoxP3 mRNA in PBMC from atherosclerotic patients, reflected in the serum by decreased TGF-β protein levels when measured by ELISA.…”
mentioning
confidence: 52%
“…However, the number and function of these cells decreases both in plaques and in circulation as disease progresses, consistent with a breakdown in tolerance and the appearance of proinflammatory T cells (9)(10)(11)(12). The Li study confirmed this decline in circulating Treg numbers alongside the expression levels of TGF-β and FoxP3 mRNA in PBMC from atherosclerotic patients, reflected in the serum by decreased TGF-β protein levels when measured by ELISA.…”
mentioning
confidence: 52%
“…In addition to the human Th1/Th2 balance, the balance between Treg and Th17 cells [11] is critical for controlling the development of autoimmune and inflammatory responses. The Th17/Treg balance has an important role in the development of a variety of human diseases, including cancer, inflammation, and autoimmune diseases [12][13][14][15]. Galon [16] suggested that an elevated Th17/Treg ratio may be a severe marker of autoimmune disease, inflammatory disease, and allergic disease, indicating that the equilibrium of different types of immune cells can be used to better predict clinical prognosis in patients.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, a significant negative correlation between Th17 and Treg cell frequencies has been found in the circulation of patients with unstable carotid artery lesions. 45 This imbalance between Th17 cells and Tregs has been confirmed 46 , suggesting one of the mechanisms through which Tregs regulate atherosclerosis is the inhibition of Th17 cells. Interestingly, the ability of Treg to suppress Th1 or Th17 responses may require differential stimulation of the Treg by IFNγ and IL-17 vs. IL-10, respectively.…”
Section: Introductionmentioning
confidence: 88%